TEORITISASI DIALOG LINTAS AGAMA DALAM KAJIAN HUBUNGAN INTERNASIONAL KONTEMPORER - Renaldo Benarrivo (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2022)
Interfaith dialogue has not gained a strategic place in the context of the study of international relations yet, even though its existence has practically provided new dynamics in the constellation of contemporary international relations. Not only that, interfaith dialogue also has sufficient theoretical urgency as a academics study that needs to be continuously developed. The debate between realism and idealism continues to develop in contemporary international relations studies. This development is influenced by the expansion of the meaning of actors who not only talk about state actors but also non-state actors, the expansion of the issues was originally focused on hard political issues but also focus to the discussion on low political issues, as well as how the interaction between actors with the religious discussion of these issues has created varied patterns of relations between actors in the study of international relations. This study attempts to place the phenomenon of interfaith dialogue theoretically in the study of international relations through a rational perspective, by seeking a middle ground between the realism and idealism debates. The English School approach, foreign policy, and diplomacy will try to be presented so that the theoretical position of inter-religious dialogue will become clear as a phenomenon that continues to develop in the study of international relations. The importance of this research is to provide the possibility of a wider variety of studies in the context of international relations, so that the existence of international relations as a scientific discipline can be optimized for its contribution to analyzing social phenomena across national borders that occur and growing.